Getting expressivism out of the woods - Raskoff, SZ (Michigan Publishing, 2018)
In a recent paper, Jack Woods (2014) advances an intriguing argument against expressivism based on Moore’s paradox. Woods argues that a central tenet of expressivism—which he, following Mark Schroeder (2008a), calls the parity thesis—is false. The parity thesis is the thesis that moral assertions express noncognitive, desire-like attitudes like disapproval in exactly the same way that ordinary, descriptive assertions express cognitive, belief-like attitudes. Most contemporary defenders of expressivism seem not only to accept the parity thesis but also to rely on it to distinguish their view from subjectivism, so Woods’s argument against it poses a serious challenge to the view. In this paper, I argue that Woods’s argument is unsuccessful, but show that diagnosing precisely where it goes wrong raises interesting questions for expressivists—and metaethicists more generally—about the transparency of our moral attitudes.